(untitled) (Journal of the College of Basic Education, 2023)
The feminist prose poem with a vision of the future took its place among the different literary genres.She enjoyed her freedom and did not want to intentionally break any traditional form; And she wanted to blow up visionsnew », especially after it was linked to the fate of man; It is a kind of rebellion and freedom and means a revolution of thoughtAnd a manifestation of man’s continuous struggle against his destiny, rather than an attempt to renew the formpoetic, as long as that poem is rebellious and free from restrictions; This is more appropriate to the capabilities of the Iraqi poetContemporary and we are looking for new forms that accommodate its desires, concerns, wishes, ideas and everything related to itIn the corners of her emotional world, as well as her flight in the atmosphere of poetic space fluently sowing her seedsCreativity in the ground of a poem that gave her the freedom to write in long lines; So given to her inner rhythmsense of her femininity.